Pesan Moral pada Film Mencari Hilal: Analisis Semiotika Roland Barthes - Elvina Juniatri; Sururuddin; Mila Wahyuni (Journal of Religion and Film, 2022)
Film is one of the mass communication media which is very effective in conveying moral messages to the public. As a visual communication medium, films use moving images and audio which contain information to the audience. Movies become entertainment shows and guidance. In this research, the writer chose the film "Searching for Hilal" as the object of research. This 1 hour 33 minute film tells the journey of a conservative father and a more modern son in search of the new moon, a sign of the beginning of the month of Shawwal and the end of the month of Ramadan. Hilal is used to determine the time of Eid al-Fitr in Islam. This study aims to interpret the moral message of the film â€œSeeking Hilalâ€ using interpretive qualitative research methods. Roland Barthes' semiotic analysis, which divides meaning into denotation, connotation, and myth, is the data analysis method chosen by the writer to examine pieces of the scene seen as containing elements of moral messages. The results showed the meaning of denotation, connotation, and myths in the film "Searching for Hilal" which contains moral messages, namely: 1). Trade as Worship; 2). Da'wah Ethics; 3). Technology and Islamic Sharia; 4). Religion and Culture; and 5). Diversity in Religion.